Differences in functional activity and antigen expression of granulocytes primed in vivo with filgrastim, lenograstim, or pegfilgrastim - Ribeiro, Daniel; Veldwijk, Marlon Romano; Benner, Axel; Maier-Laufs, Stephanie; Wenz, Frederik; Ho, Anthony Dick; Frühauf, Stefan (Transfusion, 2007)
BACKGROUND: Granulocyte-colony-stimulating factor (G-CSF) is known to affect functional activity and antigen expression of neutrophil granulocytes. Beside nonglycosylated filgrastim and glycosylated lenograstim, pegylated filgrastim (pegfilgrastim) has recently been introduced for single administration into clinical use. STUDY DESIGN AND METHODS: Here, granulocytes from 27 patients with nonmyeloid malignancies were compared functionally (migration, reactive oxygen species production, and G-CSF serum levels) and phenotypically (cell surface antigen expression) before and after G-CSF administration. RESULTS: After exposure to G-CSF, chemotaxis was reduced significantly in the filgrastim group. Immunophenotypically, in vivo G-CSF-primed granulocytes were more mature in the lenograstim than in the filgrastim and to lesser extent in the pegfilgrastim groups as shown by the expression profile for CD11b, CD14, and CD16. Of note, G-CSF serum levels were similar among the groups. CONCLUSION: Our data suggest that granulocytes exposed to glycosylated G-CSF in vivo seem to resemble more closely their steady-state phenotype than after treatment with nonglycosylated and to lesser extent pegylated G-CSF.